When Bad News Arrives: Project HOPE in a Post-Factual World. (February 2018) - Cullen, Francis T.; Pratt, Travis C.; Turanovic, Jillian J.; Butler, Leah
On the basis of limited empirical evidence, advocates of Project HOPE (Hawaii's Opportunity Probation with Enforcement) have succeeded in spreading the model to a reported 31 states and 160 locations. A recent randomized control experiment across four sites has revealed negative results: no overall effect on recidivism. In this context, we examine how prominent advocates of Project HOPE have coped with the arrival of this "bad news." Despite null findings from a "gold standard" evaluation study, advocates continue to express confidence in the HOPE model and to support its further implementation. The risk thus exists that Project HOPE is entering a post-factual world in which diminishing its appeal—let alone its falsification—is not possible. It is the collective responsibility of corrections researchers to warn policy makers that the HOPE model is not a proven intervention and may not be effective in many agencies. It is also our responsibility to create a science of community supervision that can establish more definitively best practices in this area.